2004
DOI: 10.1192/bjp.184.3.251
|View full text |Cite
|
Sign up to set email alerts
|

Testimony method to ameliorate post-traumatic stress symptoms

Abstract: A remarkable drop in symptoms could not be linked directly to the intervention. Feasibility of the intervention was good, but controlling the intervention in a small rural community appeared to be a difficult task to accomplish.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(36 citation statements)
references
References 19 publications
0
36
0
Order By: Relevance
“…The empirical results of these methods exhibit diverse effects in refugees. Although Igreja et al (2004) was unable to detect a significant effect of this approach in contrast to the comparison group, and Weine et al (1998) described positive effects within an uncontrolled study, Neuner et al (2004) documented moderate effects immediately after the therapy, which then increased significantly in the one-year follow up.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The empirical results of these methods exhibit diverse effects in refugees. Although Igreja et al (2004) was unable to detect a significant effect of this approach in contrast to the comparison group, and Weine et al (1998) described positive effects within an uncontrolled study, Neuner et al (2004) documented moderate effects immediately after the therapy, which then increased significantly in the one-year follow up.…”
Section: Discussionmentioning
confidence: 63%
“…However, our approach contrasts significantly with the narrative exposure therapy (Neuner et al, 2004(Neuner et al, , 2008 and the testimony psychotherapy (Igreja, Kleijn, Schreuder, van Dijk, & Verschuur, 2004;Weine et al, 1998), which aim at confronting refugees with their traumatic experiences in a very short span of time. The empirical results of these methods exhibit diverse effects in refugees.…”
Section: Discussionmentioning
confidence: 95%
“…In addition to our previous trial of IPT-G in southwestern Uganda, 8 are RCTs by Patel et al in India, 7 Araya et al in Chile, 6 and Igreja et al 5 in Mozambique; all focusing on adults. Two of these studies used individual-based psychotherapy treatments 5,7 and reported no effectiveness, whereas the 2 group-based studies found active treatment superior to controls. The current study also supports the potential of group-based therapies.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Designed for ease of administration, it consists of 20 items covering symptoms of anxiety and mood disorders with a binary (yes/no) response scale. The SRQ-20 has been assessed across a wide range of contexts, including conflict and refugee settings in Colombia [30], Guinea Bissau [31], Mozambique [32], Rwanda [33], Uganda [34], Iran [35], Pakistan [36], and Afghanistan [37,38]. In Afghanistan, the psychometric properties of a Pashto SRQ-20 were examined by Ventevogel and colleagues [39], who reported reasonable psychometric properties but large differences across gender.…”
Section: Introductionmentioning
confidence: 99%